The regulation of market manipulation in Australia: a historical comparative perspective - Chitimira, Howard (My University, 2015)
Notably, in Australia, market abuse practices like market manipulation and other market misconduct practices are expressly prohibited under the Corporations Act as amended by the Financial Services Reform Act. In the light of this, and for the purposes of this article, a brief historical analysis of the market manipulation prohibition will be presented first. Secondly, the available penalties and remedies for market manipulation are discussed. Thereafter, possible recommendations and significant Australian anti-market abuse enforcement approaches that may be utilised in South Africa are briefly stated. Lastly, concluding remarks are provided.
Keywords: Enforcement; Market abuse; Regulation; Financial markets; Market manipulation